Changes in clinical, biochemical, immunological and integrative parameters in patients with chronic hepatitis C virus infection according to the virus genotype and the grade of activity - A. H. Lishnevska; M. D. Chemych (Zaporožskij Medicinskij Žurnal)
The aim of this study is to determine the features of the course of chronic hepatitis C virus (CHCV) infection and the dependence of changes in integrative indicators of endogenous intoxication, nonspecific immunoreactivity and inflammation on the virus genotype and the grade of activity.